Praktik Bimbingan Konseling dan Mediasi Keluarga di KUA Kecamatan Kemuning Kota Palembang - Nabila Nabila; Adelia Levira; Galuh Dwi Fajri; Kgs. M. Abu Yazid Al Bustomi; Karina Karina; Lady Diana Putri (CV. Doki Course and Training, 2025)
The family is the smallest social unit that plays a vital role in enhancing community resilience and well-being. In Islam, the ideal family is defined as one that is harmonious, loving, and compassionate. To support the formation of harmonious families, the Office of Religious Affairs (KUA) of Kemuning District, Palembang City, provides family counseling and mediation services oriented towards preventing and resolving domestic conflicts. This study uses a qualitative, descriptive-analytical approach with empirical juridical methods, utilizing in-depth interviews, observations, and documentation studies to understand family mediation practices, the role of mediators, and the factors supporting and inhibiting service success. The results show that counseling and mediation practices at the KUA are implemented systematically, integrating Islamic values ​​and marital law. These services provide a safe and persuasive dialogue space for couples to resolve conflicts, while simultaneously building awareness, responsibility, and commitment in their married lives. The effectiveness of these services is influenced by the couple's openness, the mediator's emotional and spiritual approach, and institutional policy support. Although not all conflicts are successfully resolved through this mechanism, the KUA still plays a strategic role as a preventive instrument in maintaining family resilience. This study emphasizes the importance of strengthening the capacity of mediators and cross-institutional synergy to increase the effectiveness of family counseling and mediation in realizing a harmonious, loving, and compassionate family.